Risk Assessment and Preservative Measures for Volatile Organic Compounds in Museum Showcases. (1st August 2018) - Chiantore, Oscar; Riedo, Chiara; Poli, Tommaso; Cotrufo, Giancarlo; Hohenstatt, Peter
ABSTRACT: The first step in preservative measures for artworks in airtight showcases is the exclusion of outgassing from construction materials or, at least, limitation of the emissions to a minimum acceptable level if the volatile organic compounds (VOCs) generated may be qualified as harmless. Once it is ascertained that the objects in the showcases are responsible for VOC emissions, a step forward becomes necessary, implying showcase ventilation with air flowing through active sorbent materials. Solid phase micro-extraction (SPME) followed by GC separation and MS identification has been applied for checking the outgassing characteristics of different types of materials used for the construction of airtight showcases, and the method was found particularly attractive in terms of speed and sensitivity, suitable for measurements in presence of low-emitting materials. Sampling could also be done in the case interiors, thus making possible detection and recognition of emissions from art objects within a case. A comprehensive preventive conservation scheme has been further devised by means of active air circulation within the showcase and functional sorbent materials along the flow, for complete suppression of gaseous compounds. Control of the compounds in the air flow and of their filtration efficacy was achieved by direct sampling, also using SPME fibers. Continuous monitoring of the air quality in the showcases has been developed with insertion of a photoionization detector capable of detecting the VOCs in the air by inducing molecular ionization, and measuring the generated photocurrent. The system is not selective, but gives the total concentration, reaching ppb sensitivity with high-quality data. In addition it includes temperature and humidity sensors, making the whole a useful instrument for environment control.